Elasticity and Buoyancy of Taxation in Nepal: A Revisit of the Empirical Evidence - Bhandari, Pitambar; Dangal, Madhav; Koirala, Tap Prasad; Silpakar, Sajana (NRB Economic Review, 2017)
In this paper, we use autoregressive distributed lag (ARDL) approach to cointegration developed by Pesaran et al. (1999) to estimate the elasticity and buoyancy coefficients of various revenue heads. We find that long-run buoyancy coefficients are greater than unity for all revenue heads except for custom duty whereas elasticity coefficients except for VAT are smaller than unity. Short-run buoyancy and elasticity coefficients for all revenue heads are found smaller than unity. We find OLS estimates of these coefficients to be spurious for the sample 1975-2016. These coefficients will be biased if data generating process (DGP) excludes tax exemption. All components of revenue besides income tax and VAT are found to be neutral to inflation. Empirical evidence suggests that custom reform should get top priority in the reform of revenue administration.